PENGARUH KOMPRES DINGIN TERHADAP PENURUNAN NYERI PERSALINAN KALA I FASE AKTIF DI BPS NY. MUJIYATI KABUPATEN LAMONGAN - Lilin Turlina; Nepi Vilanti Eka Ratnasari (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2015)
The aim of research to determine the effect of cold pack on the decrese of pain childbirth at 1 active phase. The study design used Pre-Eksperiment Pratest-Postes Design. The population in this research where all women who give birth in BPS Ny.Mujiyati, Amd.Keb. Sample taken by simple random sampling. Data taken by observasion and analyzed using Wilcoxon Sign Rank Test significance 0,05. The result showed that cold pack was influence on the decrase of pain childbirth at 1 active phase in BPS Ny.Mujiyati, Amd.Keb. Joto Sanur village, Tikung SubDistrict, Lamongan District, year 2013.Keywords: cold pack, painful childbirth reduction